Situation Report: Hungary, 10 July 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Prantner's Visit to World Council of Churches Headquarters in Geneva First Comments on Belgrade Conference of Nonaligned Nations Visit of Hungarian Party and Government Delegation to Bulgaria Hungarian-Soviet Agreement on Payment of Fees for Technical Documentation